Trauma, trust and social reconstruction: From broken ties to social recovery - Čorkalo Biruški, Dinka (Array, 2007)
Key concepts of post-trauma community recovery will be discussed: trauma, trust and social reconstruction. A concept of social reconstruction as a form of social recovery will be discussed as a better substitute for the concept that has been widely (mis)used – the concept of reconciliation. It will be emphasized that establishing trust is an essential precondition for individual and community recovery, asserting that it is a long-term process with specific dynamics, especially when considering highly traumatized community. Concepts of forgiveness and reconciliation will be examined in the context of social recovery ; however their intrapersonal nature will be emphasized and their usefulness for the management of post-conflict group tensions will be challenged and reconsidered. Examples from our own research will be given that studied the process of social recovery in the city of Vukovar, Croatia, as an example of the community that heavily suffered in the 1991-1995 war. A large number of victims, material destruction and severe collective trauma have changed this community that used to be highly integrated before the war into an ethnically divided community characterized by an atmosphere of deep mistrust. Boundaries between groups are clearly defined by many ethnic symbols and identity markers. Factors that prevent and facilitate community social recovery will be elaborated.